The missing [videorecording (DVD)] - Jones, Tommy Lee, 1946-; Blanchett, Cate, 1969-; Wood, Evan Rachel, 1987-; Boyd, Jenna, 1993-; Eidson, Tom, 1944- (Sony Pictures Home Entertainment, 2006)
In 19th century New Mexico, a father comes home hoping to reconcile with his daughter, Maggie. Maggie's daughter is kidnapped, forcing father and daughter to work together to get her back.